Thermochromic behavior of tellurite glasses - Celikbilek, M.; Ersundu, A. E.; Zayim, E. O.; Aydin, S. (ELSEVIER SCIENCE SA, 2015)
Thermochromic behavior of tellurite glasses in the TeO2-WO3-A(2)O (A(2)O, A = Li, Na, K) system was investigated. Transmittance in visible region, absorption edge and optical band gap energy were determined at different temperatures below glass transition temperature. Reversibility of thermochromic behavior was tested using repeated heating and cooling measurements. The absorption edge values shifted towards longer wavelengths with increasing temperature and shift rate of absorption edge was found in the range of -3.94 x 10(-4) and -8.86 x 10(-4) eV/K similar to those of conventional semiconductor materials. Band gap energy values were found to decrease with increasing temperature lying in the range 1.81-2.83 eV. Tellurite glasses showed reversible thermochromic behavior and expected to find use in thermochromic applications. Good semiconducting property of tellurite glasses is found to be the cause of thermochromism. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Tellurite glasses; Thermochromism; Semiconductor; Band gap energy; Absorption edge; OPTICAL-ABSORPTION; TEMPERATURE; GAP; COLORATION; DEPENDENCE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering